Penerapan Sistem Informasi Penjualan Baju Berbasis Android Sebagai Peningkatan Layanan Konsumen - Nurhidayati, Nurhidayati; Suhartini, Suhartini; Permana, Baiq Andriska Candra; Nur, Amri Mulliawan (Infotek: Jurnal Informatika dan Teknologi, 2024)
The development of the internet world is highly expected for the present because more and more private companies, agencies, and educational institutions are very highly in need to serve as information services. In this study, we will try to make an Android-based Jersey Shirt Sales System Application that is addressed at the Berugak Jersey Lombok Store. The Berugak Jersey Lombok shop only uses social media and manuals in marketing its products. So, most of the consumers/customers come from the people around them and the social media they use. Currently, a business field is certainly less competitive if it does not have online marketing media such as e-commerce applications/websites. The existence of an application/website will be able to expand the reach in marketing the products sold at this store. The method used in the design and manufacture of this software is the waterfall method. The purpose of this final project research is to produce a sales system application design that can make it easier for consumers to place orders/transactions at the Berugak Jersey Lombok store and as a means to promote products to be more communicative and informative, to expand the marketing area and increase the number of consumers.